2020
DOI: 10.5114/aoms.2020.98168
|View full text |Cite
|
Sign up to set email alerts
|

The effect of beinaglutide on visceral fat and bodyweight in obese type 2 diabetic patients

Abstract: Introduction: Glucagon-like peptide-1 (GLP-1) analogues could induce clinically significant weight loss in obese patients with type 2 diabetes mellitus (T2DM). Beinaglutide is a GLP-1 analogue that is fully homologous to human GLP-1. This study aims to investigate the clinical efficacy of beinaglutide in visceral fat, weight loss and blood glucose in patients with T2DM and obesity. Material and methods: One hundred and seven obese patients with T2DM, according to the World Health Organisation's (WHO) diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Recently, Gao et al [ 81 ] found that beinaglutide was more efficient than metformin at reducing a fat mass in patients of the Chinese population who were overweight and nondiabetic. The effective daily doses of beinaglutide were in the range of 0.24–0.30 mg [ 82 ].…”
Section: Novel Drugs In Obesity Treatmentmentioning
confidence: 99%
“…Recently, Gao et al [ 81 ] found that beinaglutide was more efficient than metformin at reducing a fat mass in patients of the Chinese population who were overweight and nondiabetic. The effective daily doses of beinaglutide were in the range of 0.24–0.30 mg [ 82 ].…”
Section: Novel Drugs In Obesity Treatmentmentioning
confidence: 99%